Computer Applications for Database, Education, and Ubiquitous Computing International Conferences, EL, DTA and UNESST 2012, Held as Part of the Future Generation Information Technology Conference, FGIT 2012, Gangneug, Korea, December 16-19, 2012. Proceedings - Kim, Tai-hoon.; Ma, Jianhua; Fang, Wai-chi.; Zhang, Yanchun; Cuzzocrea, Alfredo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume constitutes the refereed proceedings of the International Conferences, EL, DTA and UNESST 2012, held as part of the Future Generation Information Technology Conference, FGIT 2012, Kangwondo, Korea, in December 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of education and learning, database theory and application and u- and e-service, science and technology.
Education and learning -- Database theory and application -- U- and e-service -- Science and technology.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Software Engineering; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity